Implementing the Active Cycle of Breathing Technique (ACBT) for Managing Ineffective Breathing Pattern in a Patient with Congestive Heart Failure: A Case Study - Ardiansyah, Fakrul; Aprilina, Sindi; Suhendra, Suhendra; Baedlawi, Azhari; Amandus, Hieroniumus; Handayani, Vitria (Madago Nursing Journal, 2025)
Background: Congestive Heart Failure (CHF) is a chronic clinical syndrome characterized by the heart's inability to pump blood effectively, often leading to dyspnea due to pulmonary congestion. The Active Cycle of Breathing Technique (ACBT) is a breathing exercise designed to regulate breathing patterns, improve ventilation, and facilitate sputum clearance, which may alleviate dyspnea in CHF patients. To evaluate the effectiveness of ACBT in reducing dyspnea in a CHF patient with an ineffective breathing pattern Methods: A case study design with a nursing care approach was conducted over three days. The patient was assessed through interview and observation. A nursing diagnosis of Ineffective Breathing Pattern (SDKI D.0005) was established. Interventions included Airway Management (SIKI I.01011), semi-Fowler positioning, and ACBT administration for 15 minutes daily. Respiratory rate was measured using an oximeter, and dyspnea complaints were monitored. Results: Before the intervention, the patient complained of dyspnea with a respiratory rate of 28 breaths/minute, using accessory muscles and nasal flaring. After three days of ACBT intervention, the respiratory rate decreased to 20 breaths/minute, and the patient reported no further dyspnea. Conclusion: The ACBT intervention was effective in reducing respiratory rate and relieving dyspnea in a CHF patient with an ineffective breathing pattern. ACBT can be recommended as a non-pharmacological nursing intervention to manage dyspnea in CHF patients